Evaluation of CEMIP in diagnosis of pancreatic carcinoma in comparison with other traditional markers - Randa Ahmed El Zohne; Ahmad Kamel Mostafa Abo Zaid; Omnia Abd El Moneim; Ahmed Mohamed Soliman; Dina Mohamed Safwat; Soad A. Eltokhy (Scientific Reports)
Abstract Screening and early diagnosis of pancreatic cancer (PC) are crucial for improving its prognosis. In the current study, we aimed to evaluate the clinical utility of serum cell migration inducing protein in pancreatic cancer patients (CEMIP). This study was conducted on 50 newly diagnosed pancreatic cancer patients, aged from 49 to 77 years. The study also included 20 patients with benign intestinal diseases, and 20 apparently healthy individuals who were selected as a control group for comparison. Practical work was carried out at Clinical Pathology Department, Assiut University Hospital. All groups were subjected to thorough history taking and clinical evaluation. Radiological data and laboratory tests in addition evaluation level of carcinoembryonic antigen (CEA), cancer antigen 19 − 9 (CA19-9) and CEMIP were recorded. Pancreatic cancer group had significantly higher CEA, CA19-9 and CEMIP compared to both benign GIT diseases and control group, with (P-value < 0.001) for each. Late pancreatic cancer group had significantly higher CEA, CA19-9 and CEMIP compared to early pancreatic cancer with (P-value = 0.01). For diagnosis of PC, CEMIP was 95% sensitive and 84% specific, with AUC of 0.86 while CEA was 80% sensitive and 65% specific, with AUC of 0.80 and that of serum CA 19 − 9 was 58% sensitive and 69% specific, with AUC of 0.80. For diagnosis of early PC, CEMIP was 90% sensitive and 83% specific, with AUC of 0.72. These results are better than that of serum CEA, which was 75% sensitive and 60% specific, with AUC of 0.52 and that of serum CA 19 − 9, which was 60% sensitive and 58% specific, with AUC of 0.56. Serum CEMIP may serve as non-invasive biomarkers for diagnosis of pancreatic cancer patients in comparison to other conventional biomarkers.